2018
DOI: 10.11613/bm.2018.030712
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of clinical and laboratory parameters in the diagnosis of acute appendicitis in the adult emergency department population - a case control pilot study

Abstract: IntroductionThe evaluation of patients with suspected appendicitis strives to identify all patients with presenting symptoms while minimizing negative appendectomy rate. The aim of the study was to identify the optimal combination of clinical and laboratory parameters that should facilitate the emergency department surgeon’s definite decision.Materials and methodsThe study group comprised 120 patients with suspicion of acute appendicitis (AA). In 60 patients the AA diagnosis was confirmed intraoperatively and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Various studies have reported the diagnostic value of this parameter in distinguishing acute appendicitis. In several studies on patients with acute appendicitis; however, CRP has not been recommended for the diagnosis of acute appendicitis [ [14] , [15] , [16] ]. In another three-year study performed by Al-Abed et al on 447 patients with acute appendicitis, CRP was noted as a beneficial parameter in the diagnosis of acute appendicitis and the decision to perform surgical operation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported the diagnostic value of this parameter in distinguishing acute appendicitis. In several studies on patients with acute appendicitis; however, CRP has not been recommended for the diagnosis of acute appendicitis [ [14] , [15] , [16] ]. In another three-year study performed by Al-Abed et al on 447 patients with acute appendicitis, CRP was noted as a beneficial parameter in the diagnosis of acute appendicitis and the decision to perform surgical operation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of negative appendectomy reported about 20%. So, to diagnose appendicitis, especially in the pediatric group, imaging can be a critical tool for decreasing misdiagnosis (9,10). Ultrasonography has been verified as an early diagnostic tool in young patients to avoid radiation exposure and risk of cancer secondary to CT (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…These factors include the normal baseline haematology values, (16)(17)(18) co-morbid conditions (31,32) and stage of inflammatory process at the presentation of patients who have acute appendicitis. (33)(34)(35) It is worth noting that communicable diseases are highly prevalent in South Africa, which may affect baseline neutrophil and lymphocyte counts. These conditions include human acquired immunodeficiency virus (HIV) infection which may lead to the depletion of CD4+ T-lymphocytes (34) and therefore affect the diagnostic value of NLR.…”
Section: Discussionmentioning
confidence: 99%